Making Holocaust Memory in Finland: The Jewish Community and Conflicting Loyalties, 1944–1950s - Muir, Simo (Holocaust and genocide studies, 2023)
This article analyzes how Finnish Jews defined their position during the Second World War when Finland fought against the Soviet Union as a co-belligerent of Nazi Germany. After the Moscow Armistice in September 1944, the Jewish community’s leadership created an official narrative that transformed the community’s travails into a positive experience. They wanted to signal to the Allied forces and Jewish communities worldwide that their rights had not been violated during the war, even though Finland had been de facto allied with Nazi Germany. By doing so, they suppressed knowledge of the treatment of Jewish refugees and their deportations, as well as of their own volatile positions during the war. By inviting Marshal Mannerheim to the Helsinki synagogue in December 1944, the community helped forge Mannerheim into a national hero by honoring him for saving the Finnish Jewish community from the Holocaust. In addition, this article examines how Finnish Jews commemorated Holocaust victims vis-à-vis the commemoration of fallen Jewish soldiers in the transnational Jewish (survivor) community in the immediate postwar years.